Cambios en fuerza explosiva y agilidad tras un entrenamiento online en jóvenes jugadores de baloncesto confinados por COVID-19 - Ricart Luna, B.; Monteagudo Chiner, P.; Pérez Puchades, V.; Cordellat Marzal, A.; Roldán Aliaga, A.; Blasco Lafarga, C. (Retos: nuevas tendencias en educación física, deporte y recreación, 2021)
The closure of sports centers and suspension of training and competitions caused by COVID-19 led to a significant decrease in physical activity of high performance basketball players. The aim of this study was to investigate if a strength online training program was able to improve height and power in jumping, and to mitigate the effects of the quarantine in agility. Fifty-one elite youth basketball players (72.74 ± 13.30 kg; 1.85 ± .10 m), were divided into three age categories (Infants (U-14): 20 players, 13.45 ± .51 years; Cadets (U-16): 22 players, 15.59 ± .50 years; Juniors (U-18): 9 players, 17.00 ± .50 years) and evaluated for parameters related to body composition, explosive strength during jumping (bilateral and unilateral Abalakov test), and agility (V-Cut test). Weight and BMI were negatively affected. Explosive strength improved after the intervention (p < .001) in all variables and categories, while agility worsened significantly (p < .001), confirming that the lack of space to move and the absence of perceptual-cognitive orientation in training are important limitations, with worse consequences as age increases. Mandatory quarantine can (and should) be an opportunity for the development of basic physical skills such as strength (paying special attention to training loads), provided that a planned and specific work of reintegration into the game is carried out afterwards. Physical trainers should pay special attention to loads in confinement, as they may be insufficient for more capable and trained athletes.